On the Nörlund-Rice Integral Formula (Indian Journal of Advanced Mathematics (IJAM), 2025)
After introducing the famous Nörlund-Rice integral formula, we apply it to Laguerre polynomials, Melzak’s relation, and Stirling numbers of the second kind to obtain nice expressions.